Perceptions and experiences of nursing students and faculty members regarding implementation of the BS-Nursing program - Abdul Karim; Amarsi, Yasmin Noorali; Parpio, Yasmin Nadeem; Cassum, Laila Akber; Amirali, Munira; Rahman, Shakir (Journal of the Pakistan Medical Association, 2023)
Objectives: To explore the perceptions and experiences of nursing students and faculty members regarding the implementation of the baccalaureate nursing programme in public-sector setting. Method: The descriptive, exploratory, qualitative study was conducted at the Khyber Medical University, Peshawar, Pakistan, from April 15, 2020 to April 15, 2021, and comprised undergraduate nursing students and faculty members. Because of the coronavirus disease-2019 pandemic, the subjects were interviewed through telephonic call using a semi-structured interview guide. Data was analysed using the Creswell’s analysis approach. Findings: Of the 15 subjects, 10(66.6%) were students aged 21-24 years; 7(70%) males and 3(30%) females. The remaining 5(33.3%) subjects were faculty members aged 25-45 years and with teaching experience of 1-18 years; 2(40%) males and 3(60%) females. A total of 85 codes and 17 categories emerged under 5 major themes; programme positive impacts, curriculum revamping, students’ challenges, faculty challenges, and recommendations. The participants believed that the four-year undergraduate nursing programme would improve the profession and quality of nursing care. Some perceived challenges were also pointed out regarding the curriculum, faculty, infrastructure and learning resources. Conclusion: Through the provision of an updated curriculum, qualified teaching faculty, appropriate learning resources and proper infrastructure, the undergraduate nursing programme can be successfully implemented in Pakistan. Key Words: BS-Nursing, Perceptions and experiences of faculty, Nursing students perceptions, Nursing curriculum, Learning resources.